Kisah Langit dan Bumi dalam Al-Qur’an melalui Lirik Musik Thrash Metal dan Kombinasi Paduan Suara - M. Farand Ilalang; Hadi Susanto; Haris Natanael Sutaryo (Institut Seni Indonesia Denpasar, 2025)
Purpose: This article examines compositional strategies in the creation of a narrative program music based on Qur’anic texts, interpreted through the musical idiom of thrash metal and integrated with choral ensemble elements. The primary objective of this study is to explore how the Qur’anic narrative of the creation of the outer space and the earth can be musically interpreted through an extreme genre and an unconventional mixed ensemble structure. Method: A qualitative-interpretative methodology was employed, involving semantic and theological analysis of carefully curated verses. Result and Discussion: The compositional outcome demonstrate that the fusion of aggresive thrash metal vocals with the harmonic textures of choral voices effectively conveys both musical tension and the cosmological narrative of the Qur’an. Implication: The implications of this work point toward the emergence of new spaces in the discourse of religious and extreme music, while also serving as a deconstructive effort to challenge stigmas surrounding metal music.